GAMBARAN PENGETAHUAN DAN SIKAP PERAWAT PELAKSANA TENTANG PENERAPAN KOMUNIKASI TERAPEUTIK PADA PASIEN HALUSINASI DI INSTALASI RAWAT INAP RUMAH SAKIT JIWA ACEH - Farid Bastian; Devi Fasrah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
The canmunication between nursess and patients in inpatient rooms of Aceh Mental Hospital was not effective. The nursess often thought that they had given enough information to their patients while the patients could not understand and asked more questions the nursess. but the nursess often gave unclear information. The objective of this rescearh was to find out an overview of nursess' knowledge and attitude regarding the implementation of therapeutic communication with patients experiencing hallucinations in inpatient rooms of Aceh Mental Hospital. A descriptive - explorative design with cross-sectional study approach was used in this research. There were 106 nurses chosen as the research samples by using a total sampling technique. A 50 - item questionnaire with Guttman and Likert scales was used as the research instrument. The data were analyzed by using a univeriate data analysis and presented in a frequency distribution table. The research was conducted in 11 inpatient rooms of the hospital from August 14 to 18, 2018. The results indicate that the variable of therapeutic canmunication definition was in a good category (64.2%). that the variable of therapemic communication objective was in a good category (67.0%). That the significance of Therapeutic communication existed (65.1%), that the variable of therapeutic communication principle was in a good category (68.9%), that the variable of therapetltic communication technique was in a good category (81.1%), that the stages of therapeutic communication existed (54.7%), that the implementation of therapeutic communication was in a good category (58.5%), that the nurses' knowledge was in a good category (76.4%), and the nurses' attitude was also in a good category (55.7%). lt is suggested that the nurses enhance the quality of their nursing care, especially the one related to effective therapeutic communication.Keywords : Thempeutic Communication. Knowledge, Attitude